Effect of porous polysulfone membrane’s thickness on flux of ferum ions - Mohamed Zaimy, Nabilla (2017)
Polysulfone membrane has been widely used in removal of heavy metal from wastewater. In this research, the wastewater from electroplating industrial was used which contain high ferum ion. The existing method still need to overcome limitations of high cost film and high polymer dosage.